Influence of oral glycopeptides on the fecal flora of human volunteers: Selection of highly glycopeptide-resistant enterococci - KORTEN, VOLKAN (Oxford University Press, 1996)
Changes in fecal flora were evaluated in 22 healthy volunteers administered oral vancomycin or teicoplanin in 1989-1991 in Belgium. Evaluation of 5 colonies per subject revealed no glycopeptide-resistant enterococci in the predominant flora before glycopeptide administration; however, large numbers (mostly Enterococcus faecium) emerged by the end of the study in 14 (64%) of the subjects. Pediococci and lactobacilli also increased in number. In 1992, 40 healthy volunteers and 33 cancer patients were evaluated by plating stool samples directly onto selective media containing vancomyein; low numbers of vancomycin-resistant enterococci (<50 cfu/g) were found in 11 (28%) of the 40 and 4 (12%) of the 33 samples, respectively. DNA restriction fragment length polymorphism analysis showed that most isolates were different, but all contained vanA in Tn1546-like elements. These results indicate that vanA and Tn1546-like elements were common in Belgium as early as 1989 and that community-based individuals in that location likely form a major reservoir for glycopeptide-resistant enterococci.